The Antioxidant Activity of Avocado (Persea americana Mill) Seed Extract and Lotion Preparation - Fatmi, Mindiya; Wulandari, Asri; Sari, Bina Lohita; Honifa, .; Widjaya, Andrea Palleva (Universitas Pakuan, 2024)
Excessive exposure to free radicals can cause skin to look dry and thin. Avocado seeds are a part of the fruit that is very rarely used and is even considered waste by society. Avocado seeds are known to contain good antioxidant activity to ward off free radicals. Topical preparations that are widely used to protect the skin from exposure to free radicals, one of which is lotion preparations with natural ingredients that contain antioxidants. This research aims to determine the antioxidant activity of avocado seed extract with different concentrations, formulate avocado seed extract lotion, distribute avocado seed extract lotion preparations, and determine the antioxidant activity of avocado seed extract lotion. The method used in this research is the in vitro 2,2-diphenyl-1-picrylhydrazyl (DPPH) method. Each avocado seed was extracted with ethanol 50 %; 70 %; and 96 %. The best antioxidant results are made into cream preparations in 3 formulas, namely F1 0.01 %; F2 0.05 %; and F3 0.1 %. The best antioxidant test results were obtained from avocado seed extract with ethanol 70 % and an IC50 of 20.68 ppm with very strong antioxidant intensity. The three lotion formulations met the evaluation requirements for topical preparations and provided an antioxidant value of F1 of 128 ppm, F2 of 72 ppm, and F3 of 55 ppm. The conclusion of this research is that the highest antioxidants in avocado seed extract are found in the 70 % ethanol extract and in the formula 3 lotion preparation.